2020
DOI: 10.24018/ejbmr.2020.5.5.532
|View full text |Cite
|
Sign up to set email alerts
|

Macroeconomic Impacts of Oil Price Shocks on the Nigerian Economy

Abstract: The study investigates the macroeconomic impacts of oil price shocks in Nigeria. The study which covers a period from 1980 to 2019 made use of macroeconomic variables such as exchange rate, inflation rate, GDP while oil price is the main exogenous variable. The VAR technique of analysis is adopted and the result shows that oil price shocks do not have direct effect on the GDP but via macroeconomic variable especially exchange rate. The study indicates that exchange rate is the main intermediate variable that p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Data on GDP growth rate, inflation and exchange rate are obtained from the Central Bank of Nigeria Statistical Bulletin online da-tabase. 1 Data on Brent oil prices are from the U. S. Energy Information Administration (EIA), while data on OPEC oil production quotas are obtained from OPEC Annual Statistical Bulletin. 2 We use the GPR index as an indicator of conflict.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Data on GDP growth rate, inflation and exchange rate are obtained from the Central Bank of Nigeria Statistical Bulletin online da-tabase. 1 Data on Brent oil prices are from the U. S. Energy Information Administration (EIA), while data on OPEC oil production quotas are obtained from OPEC Annual Statistical Bulletin. 2 We use the GPR index as an indicator of conflict.…”
Section: Methodsmentioning
confidence: 99%
“…Similar research on oil price shocks was also carried out in Nigeria. Ogungbenla [1] used data from 1980 to 2019 and employed the VAR regression technique. He found that volatile oil prices had a negative impact on real GDP using variables GDP, oil price (OILP), inflation (INF), and exchange rate (EXR).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…A few other studies found evidence that the fluctuations in the global price of oil lead to exchange rate appreciations in some economies without recourse to their trade profiling. These studies include those that are targeted at net exporting countries (such as Delgado et al, 2018; Ologbenla, 2020; Kutu et al, 2021; Mukhtarov et al, 2021; Singal et al, 2019; Suliman & Abid, 2020; among others) and net importing countries (such as Ahmad et al, 2020; Hung, 2019; Liu et al, 2020; and others). Those that combined both classifications include He and Hamori (2019); Tiwari et al (2019); Jiang et al (2020); Chkir et al (2020); Nandelenga and Simpasa (2020); Yildirim and Arifli (2020); Villareal‐Samaniego (2021); Aimer and Lusta (2021); and others.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Prominent among the symmetric‐inclined techniques is the Vector Autoregressive model (VAR), which has been employed in its baseline and extensive forms. Among the users of its baseline form include Li (2021), Lin and Su (2020), Touil and Merabet (2021), Nwosa (2020), Ologbenla (2020), Delgado et al (2018); and associates the decision to its efficiency in tackling potential endogeneity among variables. Mukhtarov et al (2021), Abubakar (2019) and Ji et al (2020) used the Structural Vector Autoregressive (SVAR) method for their estimations perhaps due to the simplicity of the model in terms of avoiding structural modelling of all variables, as well as its ability to account for the feedback and relationship among all variables in the system.…”
Section: Literature Reviewmentioning
confidence: 99%